AJARAN DASA NYAMA BRATHA SEBAGAI DASAR DALAM MEWUJUDKAN KEHARMONISAN HIDUP - Aprinata Yasa, I Putu Wrastiya; I Made Krisna Mahardika; Ni Komang Sutriyanti (Guna Widya: Jurnal Pendidikan Hindu, 2025)
Ethics is an important element in life where ethics influences a person's behavior which will be internalized, practiced until it becomes a habit within him. Ethics is also a reflection of a person's self-quality. Ethics contains various kinds of standards or self-control so that a person can walk according to existing signs. The primacy of ethics in Hinduism is realized through various types of self-control teachings, including Dasa Nyama Brata, namely ten types of spiritual (mental) stage of self-control. The parts are: Dhana (giving alms), Ijya (worship of the gods), Tapa (restraint of sexual desires), Dhyana (contemplating God), Swadhyaya (studying the Vedas), Upasthanigraha (controlling sexual desires), Brata (restraint of lust for food), Upawasa (fasting), mona (not making sounds or uttering words), Snana (worshiping the Tri Sandhya). Knowing its virtues is very important to study and make efforts to internalize it so that you always carry out karma according to the signs recommended in the Veda. Although in its implementation there are various challenges and upheavals in the era of increasingly massive globalization. If the application of Dasa Nyama Brata can be maximized then a person can achieve harmony.